Identifikacija genskih kandidata povezanih sa sindromom iritabilnog kolona - Milovac, Irina; Vidović, Vanja; Ramić, Jasmin; Lojo-Kadrić, Naida; Hadžić, Maida; Mavija, Zoran; Vidović, Stojko; Pojskić, Lejla (Scripta Medica, 2022)
Background/Aim: Irritable bowel syndrome (IBS) belongs to the gastrointestinal disorders characterised by abdominal discomfort and pain, altered constipation, diarrhoea and stomach distension. The aim was to assess relationship between the selected genetic polymorphisms with IBS, their combined genotype effect as well as to assess a difference in the distribution of allele and genotype frequencies of selected loci between case and control group.Methods: This was a prospective study which included 29 participants, 20 individuals diagnosed with IBS based on Rome III criteria and 9 healthy individuals. The study analysed the selected genetic polymorphisms as possible risk factors for IBS according to the model of the case-control study. Genotyping was performed for FKBP5, DRD2 and DAT polymorphisms qualified as risk factors for IBS in previous researches. Results: The results revealed a significant association between DAT polymorphism with IBS, both, at the allelic level (p = 0.006) and genotype level (p = 0.031). Individuals with 434 allelic variant in the genotype have six time higher probability for developing IBS, in comparison to the individuals without this allelic variant. The statistical association between other analysed polymorphism and IBS was not reached. The analysis of combined effects of selected polymorphisms revealed no association with IBS, except FKBP5 and DAT which result was at the level of statistical significance (p = 0.05).Conclusion: Further analysis which would include DAT polymorphism with larger sample size, as well as other genes involved in dopamine neurotransmitter system would be of great interest to define closer conclusion of IBS aetiology.